2019
DOI: 10.7150/jca.29765
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Mechanisms of Areca Nuts in Oral Carcinogenesis: the Molecular Pathology from Precancerous Condition to Malignant Transformation

Abstract: Oral cancer is one of the most frequent malignant diseases worldwide, and areca nut is a primary carcinogen causing this cancer in Southeast Asia. It has been widely reported that areca nut induced several cytotoxic effects in oral cells, including ROS generation, inflammation, tissue hypoxia, DNA damage, and cell invasion. Recently, through chronic exposure model, more extensive pathological effects due to areca nut have been found. These include the induction of autophagy, promotion of epithelial-mesenchymal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 112 publications
(179 reference statements)
1
52
0
Order By: Relevance
“…Results from this study imply the association of low SES with chewing habits and late stage presentation supported by different studies. Areca nut is the fourth most common psychoactive substance used in the world [45] and habitual areca nut chewers present with more aggressive cancer phenotypes, high rates of metastasized cancer, recurrence, and poor patient survival [46]. Though the association of areca nut chewing with late stage tumor remains largely unexplored, this is just an observation with no definite answers.…”
Section: Plos Onementioning
confidence: 99%
“…Results from this study imply the association of low SES with chewing habits and late stage presentation supported by different studies. Areca nut is the fourth most common psychoactive substance used in the world [45] and habitual areca nut chewers present with more aggressive cancer phenotypes, high rates of metastasized cancer, recurrence, and poor patient survival [46]. Though the association of areca nut chewing with late stage tumor remains largely unexplored, this is just an observation with no definite answers.…”
Section: Plos Onementioning
confidence: 99%
“…However, it contains a relatively low content of arecanut (12.5% of the mixture) when compared to the CBQ. Both epidemiological and animal studies have shown an association between arecanut and development of oral potentially malignant disorders (OPMDs) and the risk of oral cancer [ 68 , 71 , 72 ]. However, it has been demonstrated that such association depends on the frequency and the dose of arecanut consumption [ 71 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…49,50 Furthermore, areca nut-induced chemoradioresistance results from the upregulation of ATP-binding cassette subfamily G member-2 (ABCG-2), a drug-efflux pump and a stem cell marker. 22,49,50 Oral cancers among habitual areca nut chewers demonstrate an aggressive phenotype, chemoradioresistance and a much lower 5-year survival rate than those without areca habits. 18 Studies on oral premalignant lesions have shown that CSC markers, such as ABCG-2 and Bmi-1, predict the transformation of oral leukoplakia to cancer.…”
Section: Alterations In the Expression Pattern Of Om-scms In Osf Opmmentioning
confidence: 99%
“…Other stemness markers, such as CD44, CD133, glucose-regulated protein 78 (Grp-78), Grp-96, Oct-4, Nanog and SOX2, are upregulated upon exposure to areca nut and correlate with worse prognosis in areca nut-induced cancers. 49 , 50 Furthermore, areca nut-induced chemoradioresistance results from the upregulation of ATP-binding cassette subfamily G member-2 (ABCG-2), a drug- efflux pump and a stem cell marker. 22 , 49 , 50 Oral cancers among habitual areca nut chewers demonstrate an aggressive phenotype, chemoradioresistance and a much lower 5-year survival rate than those without areca habits.…”
Section: Alterations In the Expression Pattern Of Om-scms In Osf Opmmentioning
confidence: 99%